Acute complete bilateral ophthalmoplegia and ptosis without ataxia or areflexia associated with serum anti‐GQ1b antibody. Issue 6 (30th August 2017) - Tsuzaki, Koji; Tatsuno, Kentaro; Inoue, Manabu; Tachibana, Naoko; Hamano, Toshiaki
Abstract: We report the case of a 65‐year‐old woman who presented with acute complete bilateral ophthalmoplegia and ptosis. Deep tendon reflexes were normal and there were no signs of ataxia. On laboratory examination, the patient had vitamin B1 deficiency; however, symptoms did not improve after fursultiamine administration. Thereafter, it was found that the patient was seropositive for anti‐ganglioside Q1b immunoglobulin G antibody, and she was diagnosed with acute ophthalmoplegia and ptosis associated with anti‐ganglioside Q1b immunoglobulin G antibody. The patient's symptoms improved gradually without further treatment over the next several months. Ataxia and areflexia were not observed during the clinical course.